Penerapan Model Pembelajaran Problem Based LearningUntuk Meningkatkan Kemampuan Berpikir Kritis SiswaMata Pelajaran Ekonomi Kelas Xi Ips 2Sma N 2 Sukoharjo Tahun - Donovan, Ronny; , Drs. Djumali, M.Pd (2016)
The aim of this study is to improve students' critical thinking ability through learning model Problem Based Learning (PBL). The type of this study was classroom action research (CAR) in two cycles. The subjects of this research were the teachers and 35 students of XI IPS 2 SMA N 02 Sukoharjo. The methods of collecting data in this research were interview, observation, and documentation. The techniques of collecting data were data reduction, reporting data, and taking conclusion. The result of the study showed there was critical thinking improvement in the subject of economic. It can be seen through the following indicators. 1) Students could distinguish fact, non fact, and opinion. Before the action 57.14% and after the action became 100%. 2) Students could distinguish definite conclusion and temporary conclusion. Before the action 37.14% and after the action became 91.42%. 3) Students could test the level of trust. Before the action 37.14% and after the action became 88.57%. 4) Students could distinguish relevant and non relevant information. Before the action 31.42% and after the action became 82.85%. 5) Students were able to make decision. Before the action 71.42% and after the action became 100%. 6) Students could identify cause and effect. Before the action 31.42% and after the action became 85.71%. 7) Students could consider other knowledge. Before the action 14.28% and after the action became 85.71%. 8) Student could test questions they have. Before the action 11.42% and after the action became 82.85%. The conclusion of this research is learning model Problem Based Learning (PBL) could improve students' critical thinking ability of XI IPS 2 SMA N 02 Sukoharjo in the economic subject.